Calcium and gibberellic acid in litchi fruits cracking (Litchi chinensis Soon.) cultivar Mauritius - Martínez Bolaños, Misael; Martínez Bolaños, Luciano; Guzmán Deheza, Antonio; Gómez Jaimes, Rafael; Reyes Reyes, Ana Laura (Revista Mexicana de Ciencias Agrícolas, 2017)
Litchi is grown in México in the states of Veracruz, Oaxaca,  Sinaloa, San Luis Potosí, Puebla, Chiapas and Michoacán.  Being the most commercialized cultivars Brewster and  Mauritius. One of its main problems is the pericarp cracking  in fruits, which diminishes the yield and quality in the  Mauritius cultivar production. The research was carried out  in 2011-2012; the incidence of cracking was evaluated in  four commercial plots of Mauritius cultivar of the following  Oaxaca municipalities: Loma Bonita, San Juan Cotzocón,  San Juan Yaveo and Santa María Jacatepec. A correlation  was made between temperature, relative humidity, solar  radiation and the incidence of cracked fruits, and the  nutritional content of pericarp, pulp and seed of cracked and  asymptomatic fruits was evaluated. The incidence of cracked  fruits was evaluated in eight treatments: 1) absolute control;  2) gibberellic acid (AG) 25 ppm (BioGip®); 3) AG 50 ppm;  4) AG 100 ppm; 5) AG 200 ppm; 6) Calcium (Ca) 50 mmol  L-1 (Poliquel Ca®); 7) Ca 100 mmol L-1; and 8) Ca 200 mmol  L-1. The incidence of cracked fruits was observed from the  aril development until commercial maturity of the fruit,  with maximum incidence of 7.31 - 15.3% at commercial  maturity. Asymptomatic fruits showed higher boron content in the pulp than the cracked fruits. The period and intensity  of light hours had a high correlation with the incidence of  fruit cracking. Calcium applications at doses of 50, 100 and  200 mmol L-1, during and after fruit bunching, reduced the  incidence percentage of cracked fruits at harvest time.
Keywords: litchi; nutrition; pericarp; radiation